EFFECTIVENESS OF WASTE MANAGEMENT AS A SOURCE OF ELECTRICAL ENERGY IN TPA BENOWO, SURABAYA CITY - Wilya Sulistiarini; Tukiman - (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
Waste management is very important to achieve a clean and healthy environmental quality, thus waste must be managed as well as possible by implementing established planning and regulations so that things that are negative for life do not happen. Reuse accompanied by reduced usage is an effective step to overcome existing problems and the lifestyle of the community must be changed with existing waste to be processed into something of value, therefore the government has created innovations in overcoming waste problems, namely using environmentally friendly technology or PLTSa Garbage power plant). The purpose of this research is to describe, know and analyze the effectiveness of waste management as a source of electrical energy in TPA Benowo, Surabaya. This research is a form of research conducted with a qualitative approach. Data collection techniques in this study are interviews, observation and documentation to obtain information related to environmentally friendly technological innovations. The results show that the effectiveness of waste management as a source of electrical energy in TPA Benowo, Surabaya city is effective and is running according to existing regulations by measuring indicators from Riant Nugroho's theory so that with Appropriate the effectiveness of established policies can turn waste into useful goods. with environmentally friendly technology.